Pengaruh Progressive Muscle Relaxation Terhadap Kualitas Tidur Pada Pasien Kanker Yang Menjalani Kemoterapi di SMC Telogorejo - Siti Khasanah; Musa’adah Musa’adah; Dwi Fitriyanti (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2023)
Cancer is a condition in which cells have lost their normal controls and mechanisms, resulting in abnormal, fast and uncontrolled growth and threatens the lives of sufferers. Central Java ranks second in the highest cancer prevalence in Indonesia with a prevalence of 2.1% after Yogyakarta (4.9%). Meanwhile in the city of Semarang, there were 3,590 cancer sufferers recorded. At the SMC Telogorejo Hospital, cancer cases were recorded in 2020 as many as 1361 patients, then in 2021 there were 1261 patients and in 2022 there were 1125. The management of cancer patients is one of them with chemotherapy which can have a sleep disturbance effect. Handling sleep disorders can be done with a non-pharmacological approach, one of which is Progressive Muscle Relaxation. This study aims to determine the effect of Progressive Muscle Relaxation on sleep quality in cancer patients undergoing chemotherapy at the SMC Telogorejo Hospital. This research is a quasi-experimental design with one group pre test-post test design. the sample in this study amounted to 39 respondents using a purposive sampling technique. The results of the study based on the Wilcoxon test showed that there was an effect of progressive muscle relaxation on the sleep quality of cancer patients undergoing chemotherapy at SMC Telogorejo (p = 0.000), where the sleep quality of patients before being given progressive muscle relaxation averaged 7.85 in the category of poor sleep quality, then after being given progressive muscle relaxation an average of 4.26 was obtained in the category of good sleep quality. Therefore nurses need to apply Progressive Muscle Relaxation as a relaxation method for treating sleep disorders.